Exploring Perceived Utility of Living vs. Dying in Relation to Suicidal Ideation Over Time - Keyne C. Law; Megan L. Rogers; Yu‐Chin Lin; Brian W. Bauer (Journal of Clinical Psychology, 2026)
ABSTRACT Introduction Using the concept of games against nature from decision theory, this study explored whether the perceived utility of living and the perceived utility of dying were related to an individual's desire to live, desire to die, and suicidal ideation. Methods One hundred thirty‐eight participants listed their perceived costs and benefits associated with living and dying and rated their importance. They also answered questions about their desire to live, desire to die, and suicidal ideation. We tested whether perceived utility (ratio of benefits to costs) of living and dying were associated with participants' desire to live, desire to die, and suicidal ideation at baseline and 1 week later. Results Cross‐sectionally, benefits of living, costs of living, and benefits of dying were each associated with desire to live, desire to die, and suicidal ideation, and the perceived utility of living and dying interacted in relation to all three outcomes. At 1‐week follow‐up, the utility ratios and most of the associations found in the cross‐sectional analyses were no longer significant after adjusting for baseline levels of each outcome; the exception was perceived costs of living, which predicted lower desire to live over and above baseline desire to live. Conclusion Findings provide preliminary, primarily cross‐sectional support for using the perceived utility framework as a lens for understanding suicidal ideation and point to perceived costs of living as a candidate target for future prospective and intervention research.